Preparation method of hollow microsphere silicon carbide composite wave-absorbing material
By preparing hollow microsphere silicon carbide composite absorbing materials, using phenolic resin and carbon layer structures, combined with carbon nanofiber layers, the problem of weak dielectric properties of silicon carbide is solved, and the absorbing performance and electromagnetic wave absorption capacity are significantly improved.
Patent Information
- Application Number
- CN202411221999.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-02
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2044-09-02
AI Technical Summary
Silicon carbide has weak dielectric properties as a wave absorbing material, resulting in poor performance of the prepared wave absorbing material.
By preparing hollow microsphere silicon carbide composite absorbing materials, phenolic resin is used to form a hollow structure, combined with the first and second carbon layers, introducing conductive loss and polarization loss mechanisms, and enhancing the absorbing performance through the carbon nanofiber layer.
It improves the absorbing performance of composite absorbing materials, enhances the absorption capacity of electromagnetic waves, extends the propagation path of electromagnetic waves, and reduces reflections.
Smart Images

Figure CN119330356A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of absorbing materials, and in particular to a method for preparing a hollow microsphere silicon carbide composite absorbing material. Background Art
[0002] With the advancement of electronic technology, more and more electronic technology products have entered human life. While enjoying the development of science and technology, humans are also facing the electromagnetic pollution caused by electronic technology products. In traditional methods, microwave absorbing materials (MAMs) are considered to be functional materials with better ability to weaken the effect of electromagnetic waves. Microwave absorbing materials can convert electromagnetic waves into Joule heat through dielectric loss and magnetic loss, and interfere with each other to cancel each other, thereby suppressing or eliminating electromagnetic radiation.
[0003] At present, most microwave absorbing materials have compatible magnetic and dielectric properties to achieve good impedance matching and strong electromagnetic attenuation capabilities. For example, microwave absorbing materials formed by composites such as Fe / C, Co / C, Ni / C, and Fe / Co / C, but the above materials containing magnetic metals are susceptible to corrosion and oxidation, and are difficult to provide long-term service in some harsh environments, such as exposure to sunlight, acid rain, and seawater.
[0004] Silicon carbide (SiC) is a nanomaterial with diverse micromorphologies and rich crystal forms. Due to its excellent physical, chemical, electrical and optical properties, it has become a good raw material for the preparation of catalysts, semiconductors, functional ceramics and high-frequency electronics. Silicon carbide also has certain acid and alkali resistance and good environmental tolerance to harsh environments. This gives silicon carbide certain advantages in the preparation of microwave absorbing materials. However, silicon carbide has a wide bandgap, slow electron migration, and weak dielectric properties, and the prepared microwave absorbing materials have poor performance. Summary of the invention
[0005] The embodiment of the present application provides a method for preparing a hollow microsphere silicon carbide composite absorbing material, which aims to improve the problem that silicon carbide as an absorbing material has weak dielectric properties and the prepared absorbing material has poor performance.
[0006] In the first aspect, the embodiment of the present application provides a method for preparing a hollow microsphere silicon carbide composite wave absorbing material, including: mixing deionized water, anhydrous ethanol and ammonia water, adding a surfactant, stirring evenly, and then adding a phenolic resin and a formaldehyde solution to mix to obtain a first mixed solution. Provide a silicon source, add the silicon source to the first mixed solution, stir and seal, and react at a first preset temperature for a preset time to obtain a second mixed solution, centrifuge the second mixed solution to obtain a first composite, and perform a carbonization treatment on the first composite to obtain a silicon dioxide / carbon hollow microsphere. Provide purified bacterial cellulose, mix the bacterial cellulose with the silicon dioxide / carbon hollow microspheres, and then freeze-dry to obtain a second composite. Mix the second composite with magnesium powder and grind to obtain a first powder, and perform a secondary carbonization treatment on the first powder to obtain a hollow microsphere silicon carbide composite wave absorbing material.
[0007] In some embodiments, providing purified bacterial cellulose includes: soaking the bacterial cellulose in an alkaline solution with a concentration of 0.2 mol / L to 0.5 mol / L, and bathing it in water at a temperature of 60°C to 100°C for 2h to 4h, and then washing the bacterial cellulose soaked in the alkaline solution with deionized water until it is neutral, to obtain the purified bacterial cellulose.
[0008] In some embodiments, the silicon source is added to the first mixed solution, stirred, sealed, and reacted at a first preset temperature for a preset time to obtain a second mixed solution, and the second mixed solution is centrifuged to obtain the first complex, including: adding the silicon source to the first mixed solution, stirring, sealing, and reacting at a temperature of 80°C to 120°C for 20h to 30h to obtain the second mixed solution. The second mixed solution is cooled to 20°C to 25°C, and the cooled second mixed solution is centrifuged to obtain a precipitate, and the precipitate is washed 3 to 5 times with anhydrous ethanol and deionized water, and the washed precipitate is placed in a drying oven at a temperature of 50°C to 80°C for 10h to 15h to obtain the first complex.
[0009] In some embodiments, subjecting the first composite to a carbonization treatment includes placing the first composite in an inert gas environment and carbonizing it in a tubular furnace at a temperature of 600° C. to 1000° C. for 2 to 3 hours, wherein the heating rate of the tubular furnace is 5° C. / min to 15° C. / min.
[0010] In some embodiments, the secondary carbonization treatment of the first powder includes: placing the first powder in an inert gas environment and carbonizing it in a tubular furnace at a temperature of 600°C to 1000°C for 2h to 3h, and the heating rate of the tubular furnace is 5°C / min to 15°C / min.
[0011] In some embodiments, the silicon source includes at least one of ethyl orthosilicate, methyl orthosilicate, methyltrimethoxysilane, and ethyltriethoxysilane.
[0012] In some embodiments, the surfactant includes at least one of cetyltrimethylammonium chloride, cetyltrimethylammonium bromide, and dodecyltrimethylammonium chloride.
[0013] In some embodiments, the mass ratio of the second composite to the magnesium powder is (6:1) to (10:1).
[0014] In some embodiments, the phenolic resin is added in an amount of 12 g / L to 18 g / L. The silicon source is added in an amount of 80 ml / L to 100 ml / L.
[0015] In some embodiments, the inert gas includes nitrogen and / or argon.
[0016] Different from the related art, the embodiment of the present application provides a method for preparing a hollow microsphere silicon carbide composite wave absorbing material. After the phenolic resin wrapped inside the first composite is carbonized, the phenolic resin dehydrates and decomposes to form a hollow structure of silicon dioxide / carbon hollow microspheres. The hollow structure is conducive to reducing impedance mismatch and improving the wave absorbing performance of the composite wave absorbing material, so that electromagnetic waves are scattered and reflected multiple times inside the microspheres, increasing the propagation path and absorption opportunity of electromagnetic waves. The first powder is carbonized twice to form a hollow microsphere SiC / C / CNF composite wave absorbing material. The first carbon layer and the second carbon layer combined with silicon carbide can introduce more loss mechanisms, such as conductivity loss, polarization loss, etc., enrich the energy loss mode in the wave absorbing process, and improve the wave absorbing performance. After carbonization, bacterial cellulose forms a carbon nanofiber layer distributed in the outermost layer of the hollow microsphere silicon carbide composite wave absorbing material. The pores and fibers of the carbon nanofiber layer can effectively capture the incident electromagnetic waves, increasing the initial contact and interaction opportunities between the electromagnetic waves and the hollow microsphere SiC / C / CNF composite wave absorbing material. The carbon nanofiber layer can increase the impedance matching with the air, reduce the reflection of electromagnetic waves, and allow more electromagnetic waves to enter the composite absorbing material for loss. In addition, the incident electromagnetic waves will undergo multiple scattering in the carbon nanofiber layer, extending the propagation path of the electromagnetic waves in the composite absorbing material and increasing the probability of electromagnetic waves being absorbed. Carbon nanofibers also have good electrical conductivity, which can enhance the electrical loss on the surface of the composite absorbing material, convert electromagnetic wave energy into heat, so that more electromagnetic waves are absorbed, and improve the absorbing performance of the composite absorbing material. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] One or more embodiments are exemplarily described by corresponding drawings, which do not constitute limitations on the embodiments. Elements with the same reference numerals in the drawings represent similar elements, and the figures in the drawings do not constitute proportional limitations unless otherwise stated.
[0018] Figure 1 It is a flow chart of a method for preparing some hollow microsphere silicon carbide composite absorbing materials provided in an embodiment of the present application;
[0019] Figure 2 Schematic diagram of the structure of some hollow microsphere silicon carbide composite absorbing materials provided in the embodiments of the present application. DETAILED DESCRIPTION
[0020] In order to make the purpose, technical solution and advantages of the present application more clearly understood, the present application is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.
[0021] In the description of the embodiments of the present application, the technical terms "first", "second", etc. are only used to distinguish different objects, and cannot be understood as indicating or implying relative importance or implicitly indicating the number, specific order or primary and secondary relationship of the indicated technical features. In the description of the embodiments of the present application, the meaning of "several" and "multiple" is more than two, unless otherwise clearly and specifically defined.
[0022] In the description of the embodiments of the present application, the term "and / or" is only a description of the association relationship of the associated objects, indicating that there may be three relationships. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in this article generally indicates that the associated objects before and after are in an "or" relationship.
[0023] Reference to "embodiment" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiment may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. In addition, the technical features involved in the different embodiments of the present application described below may be combined with each other as long as they do not conflict with each other.
[0024] In the first aspect, the present application provides a method for preparing a hollow microsphere silicon carbide composite wave absorbing material, please refer to Figure 1 , Figure 1 This is a flow chart of a method for preparing some hollow microsphere silicon carbide composite wave absorbing materials provided in the embodiments of the present application. The preparation method comprises the following steps:
[0025] Step S1: after deionized water, anhydrous ethanol and ammonia water are mixed, a surfactant is added, the mixture is stirred evenly, and then a phenolic resin and a formaldehyde solution are added and mixed to obtain a first mixed solution.
[0026] Surfactant is a substance that can significantly reduce the surface tension of liquid, promote the dispersion of phenolic resin in the system, and form a stable emulsion or reduce the aggregation and precipitation of phenolic resin in the system. For example, the surfactant includes at least one of hexadecyltrimethylammonium chloride, hexadecyltrimethylammonium bromide, and dodecyltrimethylammonium chloride.
[0027] Phenolic resin is a synthetic resin, which is formed by the polycondensation of phenolic compounds and aldehyde compounds under the action of a catalyst. Generally speaking, the carbon content in phenolic resin is usually around 70% to 80%. Due to the high carbon content of phenolic resin, during the carbonization process, as the temperature rises, the phenolic resin will gradually lose the adsorbed moisture and some small molecular substances, and the resin will begin to thermally decompose. As the temperature continues to rise, the macromolecular chain of the resin will break and decompose to produce some gas products such as carbon monoxide, carbon dioxide, methane, etc. The final calcined product is mainly carbonaceous material.
[0028] In some embodiments, the phenolic resin is added in an amount of 12 g / L to 18 g / L.
[0029] Step S2: providing a silicon source, adding the silicon source to the first mixed solution, stirring and sealing, and reacting at a first preset temperature for a preset time to obtain a second mixed solution, centrifuging the second mixed solution to obtain a first complex, and subjecting the first complex to a carbonization treatment to obtain silicon dioxide / carbon hollow microspheres.
[0030] The silicon source is mixed with the first mixed solution, and the silicon source can react with the phenolic resin in the first mixed solution to obtain a brown first composite. The first composite is wrapped with phenolic resin, and part of the phenolic resin is attached to the outer surface of the first composite. The first composite is carbonized at high temperature to obtain silicon dioxide / carbon hollow microspheres. Please refer to Figure 2 After the phenolic resin wrapped inside the first composite is carbonized, the phenolic resin dehydrates and decomposes to form a hollow structure 131 of the silica / carbon hollow microsphere 13, and the phenolic resin forms a first carbon layer 11 on the inner wall of the silica / carbon hollow microsphere 13 after carbonization. Part of the phenolic resin attached to the outer surface of the first composite forms a second carbon layer 12 on the outer wall of the silica / carbon hollow microsphere 13.
[0031] The first carbon layer 11 and the second carbon layer 12 have a special microstructure, such as porous, nano-scale structure, etc. It can enhance the scattering and reflection of electromagnetic waves, extend the propagation path of electromagnetic waves in the composite absorbing material, and improve the absorption probability of electromagnetic waves. In addition, the first carbon layer 11 and the second carbon layer 12 are composed of carbon materials, which have excellent dielectric properties and can effectively interact with electromagnetic waves. Through dielectric loss, the electromagnetic wave energy is converted into other forms of energy such as heat, thereby reducing the electromagnetic radiation of electromagnetic waves. The first carbon layer 11 and the second carbon layer 12 have a relatively low density and good chemical stability, which is convenient for use in some application scenarios with strict weight restrictions, such as aerospace, transportation and other fields.
[0032] The hollow structure 131 of the silicon dioxide / carbon hollow microsphere 13 is conducive to reducing impedance mismatch and improving the absorbing performance of the composite absorbing material. The hollow structure 131 can also reduce the density of the composite absorbing material, thereby reducing the weight of the composite absorbing material, making the composite absorbing material lightweight. The hollow structure 131 can also cause electromagnetic waves to generate multiple scattering and reflections inside the microsphere, increasing the propagation path and absorption opportunity of the electromagnetic waves.
[0033] In some embodiments, a silicon source is added to a first mixed solution, stirred, and then sealed, and reacted at a first preset temperature for a preset time to obtain a second mixed solution, and the second mixed solution is centrifuged to obtain a first complex, including: adding a silicon source to a first mixed solution, stirring, and then sealing, and reacting at a temperature of 80°C to 120°C for 20h to 30h to obtain a second mixed solution. The second mixed solution is cooled to 20°C to 25°C, and the cooled second mixed solution is centrifuged to obtain a precipitate, and the precipitate is washed 3 to 5 times with anhydrous ethanol and deionized water, and the washed precipitate is placed in a drying oven at a temperature of 50°C to 80°C for 10h to 15h to obtain a first complex.
[0034] In some embodiments, the silicon source includes at least one of ethyl orthosilicate, methyl orthosilicate, methyltrimethoxysilane, and ethyltriethoxysilane. The amount of the silicon source added is 80 ml / L to 100 ml / L.
[0035] In some embodiments, subjecting the first composite to a carbonization treatment comprises: placing the first composite in an inert gas environment, carbonizing it in a tube furnace at a temperature of 600° C. to 1000° C. for 2 to 3 hours, and the heating rate of the tube furnace is 5° C. / min to 15° C. / min. The inert gas includes nitrogen and / or argon.
[0036] Step S3: providing purified bacterial cellulose, mixing the bacterial cellulose with silica / carbon hollow microspheres and freeze-drying the mixture to obtain a second composite.
[0037] Bacterial cellulose is a natural polymer material synthesized by microorganisms. It is cellulose produced by certain bacterial strains, such as Acetobacter xylinum, under specific culture conditions. Bacterial cellulose has a fine three-dimensional network structure, and the fiber diameter is usually at the nanometer level. Bacterial cellulose has a high degree of crystallinity and excellent mechanical properties. The main component of bacterial cellulose is cellulose, which has a high carbon and oxygen content. The carbon nanofibers obtained after carbonization have higher mechanical strength and higher chemical stability. In addition, bacterial cellulose has a wide range of sources, and its production is not restricted by seasons and geographical environments, making it environmentally friendly.
[0038] The bacterial cellulose is mixed with the silica / carbon hollow microspheres and then freeze-dried. Freeze-drying helps promote the attachment of the bacterial cellulose to the surface of the silica / carbon hollow microspheres to form a more compact and stable second complex.
[0039] In some embodiments, providing purified bacterial cellulose includes soaking the bacterial cellulose in an alkaline solution with a concentration of 0.2 mol / L to 0.5 mol / L, and bathing the bacterial cellulose at a temperature of 60°C to 100°C for 2h to 4h, and then washing the bacterial cellulose soaked in the alkaline solution with deionized water until neutral, to obtain purified bacterial cellulose. The alkaline solution can be a strong sodium oxide solution, a potassium hydroxide solution, etc. The alkaline solution can remove impurities such as protein and pectin remaining in the bacterial cellulose, so that the bacterial cellulose is purified.
[0040] In some embodiments, purification of bacterial cellulose also includes acid treatment, enzyme treatment, ultrasonic treatment, etc.
[0041] Step S4: mixing the second composite with magnesium powder and grinding them to obtain a first powder, and performing a secondary carbonization treatment on the first powder to obtain a hollow microsphere silicon carbide composite absorbing material.
[0042] The secondary carburization treatment can carburize silicon dioxide into silicon carbide. Magnesium powder is used to provide a large amount of heat for the carbonization of the second composite and promote the carbonization process. Please refer to Figure 2 Under the action of carbonization, bacterial cellulose forms a carbon nanofiber (CNF) network structure distributed in the outermost layer of the hollow microsphere silicon carbide composite absorbing material 10, namely the carbon nanofiber layer 14. Among them, the hollow microsphere silicon carbide composite absorbing material 10 is a hollow microsphere SiC / C / CNF composite absorbing material.
[0043] Silicon carbide (SiC) is an inorganic non-metallic material composed of silicon and carbon. It has excellent chemical, physical, electrical and optical properties. Silicon carbide has high hardness and chemical stability, good environmental tolerance to acids, alkalis and salts, and has great development prospects in microwave absorbing materials.
[0044] The dielectric constant of silicon carbide is relatively high, which may lead to poor impedance matching with free space, resulting in more electromagnetic waves reflected on the surface of the material. The dielectric constant of carbon materials is relatively easy to adjust. The first carbon layer 11 and the second carbon layer 12 can optimize the overall impedance matching, reduce reflection, and enhance the entry and absorption of electromagnetic waves. The loss mechanism of silicon carbide itself is relatively simple. The first carbon layer 11 and the second carbon layer 12 combined with silicon carbide can introduce more loss mechanisms, such as conductivity loss, polarization loss, etc., to enrich the energy loss mode in the wave absorption process and improve the wave absorption performance.
[0045] The pores and fibers of the carbon nanofiber layer 14 can effectively capture the incident electromagnetic waves, increasing the initial contact and interaction opportunities between the electromagnetic waves and the hollow microsphere SiC / C / CNF composite absorbing material. The carbon nanofiber layer 14 can increase the impedance matching with the air, reduce the reflection of electromagnetic waves, and enable more electromagnetic waves to enter the composite absorbing material for loss. In addition, the incident electromagnetic waves will undergo multiple scattering in the carbon nanofiber layer 14, extending the propagation path of the electromagnetic waves in the composite absorbing material and increasing the probability of the electromagnetic waves being absorbed. Carbon nanofibers also have good electrical conductivity, which can enhance the electrical loss on the surface of the composite absorbing material, convert the electromagnetic wave energy into heat, and allow more electromagnetic waves to be absorbed.
[0046] In some embodiments, the second carbonization treatment of the first powder includes placing the first powder in an inert gas environment and carbonizing it in a tube furnace at a temperature of 600° C. to 1000° C. for 2 to 3 hours, and the heating rate of the tube furnace is 5° C. / min to 15° C. / min. The inert gas includes nitrogen and / or argon.
[0047] It should be noted that the above-mentioned primary carbonization refers to the first carbonization treatment, and the secondary carbonization refers to the second carbonization treatment. The above-mentioned primary and secondary refer to the operation steps, not the number of operations.
[0048] In some embodiments, the mass ratio of the second composite to the magnesium powder is (6:1) to (10:1).
[0049] The embodiment of the present application provides a method for preparing a hollow microsphere silicon carbide composite absorbing material 10. After the phenolic resin wrapped inside the first composite is carbonized, the phenolic resin dehydrates and decomposes to form a hollow structure 131 of a silicon dioxide / carbon hollow microsphere 13. The hollow structure 131 is conducive to reducing impedance mismatch and improving the absorbing performance of the composite absorbing material. It can also cause electromagnetic waves to generate multiple scattering and reflections inside the microsphere, increasing the propagation path and absorption opportunity of electromagnetic waves. The first powder is carbonized twice to form a hollow microsphere SiC / C / CNF composite absorbing material. The first carbon layer 11 and the second carbon layer 12 combined with silicon carbide can introduce more loss mechanisms, such as conductivity loss, polarization loss, etc., enrich the energy loss mode in the absorbing process, and improve the absorbing performance. Under the action of carbonization, bacterial cellulose forms a carbon nanofiber layer 14 distributed in the outermost layer of the hollow microsphere silicon carbide composite absorbing material 10. The pores and fibers of the carbon nanofiber layer 14 can effectively capture the incident electromagnetic waves, and increase the initial contact and interaction opportunities between the electromagnetic waves and the hollow microsphere SiC / C / CNF composite absorbing material. The carbon nanofiber layer 14 can increase the impedance matching between the air, reduce the reflection of electromagnetic waves, and enable more electromagnetic waves to enter the composite absorbing material for loss. In addition, the incident electromagnetic waves will undergo multiple scattering in the carbon nanofiber layer 14, extending the propagation path of the electromagnetic waves in the composite absorbing material and increasing the probability of the electromagnetic waves being absorbed. Carbon nanofibers also have good electrical conductivity, which can enhance the electrical loss on the surface of the composite absorbing material, convert the electromagnetic wave energy into heat, and allow more electromagnetic waves to be absorbed.
[0050] In a second aspect, an embodiment of the present application further provides an electronic device, which includes a hollow microsphere silicon carbide composite absorbing material prepared by the preparation method of the first aspect. The hollow microsphere silicon carbide composite absorbing material can be used for the housing of an electronic device, or a specific surface of an electronic device, to effectively block interference from external electromagnetic waves, while preventing electromagnetic waves generated inside the device from radiating outward, thereby ensuring the normal operation of the device and reducing electromagnetic pollution.
[0051] The preparation method of the hollow microsphere silicon carbide composite absorbing material is described below in conjunction with a specific embodiment:
[0052] Example 1
[0053] (1) 50 ml of deionized water, 20 ml of anhydrous ethanol and 0.3 ml of sodium bicarbonate were mixed, and then 1 g of hexadecyltrimethylammonium bromide was added, and the mixture was stirred at room temperature for 10 min. Then, 1.2 g of phenolic resin and 0.8 ml of formaldehyde were added, and the mixture was stirred to obtain a first mixed solution.
[0054] (2) Add 10 ml of tetraethyl orthosilicate to the first mixed solution, stir for 1 hour, put into 100 ml of polytetrafluoroethylene liner, and react at 100°C for 24 hours to obtain a second mixed solution. Cool the second mixture to 25°C, centrifuge the cooled second mixture to obtain a first composite. Place the first composite in a nitrogen environment, and carbonize it in a tubular furnace at a temperature of 800°C at a heating rate of 10°C / min for 2 hours to obtain silicon dioxide / carbon hollow microspheres.
[0055] (3) After mixing 1 g of silica / carbon hollow microspheres with the purified bacterial cellulose, the mixture was placed at -40°C and freeze-dried for 48 h to obtain a second composite.
[0056] (4) 5 g of the second composite material was mixed with 0.5 g of magnesium powder and ground to obtain a first powder. The first powder was placed in a magnetic boat and placed in a nitrogen environment. The mixture was carbonized in a tubular furnace at a temperature of 800 °C and a heating rate of 10 °C / min for 2 h to obtain a hollow microsphere silicon carbide composite absorbing material.
[0057] Example 2
[0058] (1) 50 ml of deionized water, 20 ml of anhydrous ethanol and 0.3 ml of sodium cetyltrimethylammonium bromide were mixed and stirred at room temperature for 10 min. Then, 1.6 g of phenolic resin and 0.4 ml of formaldehyde were added and stirred to obtain a first mixed solution.
[0059] (2) Add 8 ml of tetraethyl orthosilicate to the first mixed solution, stir for 1 hour, put it into 100 ml of polytetrafluoroethylene liner, and react at 100°C for 24 hours to obtain a second mixed solution. Cool the second mixture to 25°C, centrifuge the cooled second mixture to obtain a precipitate, wash the precipitate three times with anhydrous ethanol and deionized water, and dry the washed precipitate in a drying oven at 60°C for 12 hours to obtain a first composite. Place the first composite in a nitrogen environment and carbonize it in a tubular furnace at a temperature of 900°C at a heating rate of 10°C / min for 2 hours to obtain silica / carbon hollow microspheres.
[0060] (3) 10 g of bacterial cellulose was placed in 50 ml of a 0.5 mol / L sodium hydroxide solution and placed in a water bath at 80°C for 3 h, and then soaked in deionized water until neutral to obtain purified bacterial cellulose. 2 g of silica / carbon hollow microspheres were mixed with the purified bacterial cellulose, placed at -40°C, and freeze-dried for 48 h to obtain a second composite.
[0061] (4) 5 g of the second composite material was mixed with 0.5 g of magnesium powder and ground to obtain a first powder. The first powder was placed in a magnetic boat and placed in a nitrogen environment. The mixture was carbonized in a tubular furnace at a temperature of 900 °C and a heating rate of 10 °C / min for 2 h to obtain a hollow microsphere silicon carbide composite absorbing material.
[0062] Comparative Example 1
[0063] (1) 50 ml of deionized water, 20 ml of anhydrous ethanol and 0.3 ml of sodium cetyltrimethylammonium bromide were mixed, and 1 g of cetyltrimethylammonium bromide was added. The mixture was stirred at room temperature for 10 min, and 0.8 ml of formaldehyde was added. The mixture was stirred to obtain a first mixed solution.
[0064] (2) Add 10 ml of tetraethyl orthosilicate to the first mixed solution, stir for 1 hour, put into 100 ml of polytetrafluoroethylene liner, and react at 100°C for 24 hours to obtain a second mixed solution. Cool the second mixture to 25°C, centrifuge the cooled second mixture to obtain a first composite. Place the first composite in a nitrogen environment, and carbonize it in a tubular furnace at a temperature of 800°C at a heating rate of 10°C / min for 2 hours to obtain silica microspheres.
[0065] (3) After mixing 1 g of silica microspheres with the purified bacterial cellulose, the mixture was placed at -40°C and freeze-dried for 48 h to obtain a second composite.
[0066] (4) 5 g of the second composite material was mixed with 0.5 g of magnesium powder and ground to obtain a first powder. The first powder was placed in a magnetic boat and placed in a nitrogen environment. The mixture was carbonized in a tubular furnace at a temperature of 800 °C and a heating rate of 10 °C / min for 2 h to obtain a hollow microsphere silicon carbide composite absorbing material.
[0067] Comparative Example 2
[0068] (1) 50 ml of deionized water, 20 ml of anhydrous ethanol and 0.3 ml of sodium bicarbonate were mixed, and then 1 g of hexadecyltrimethylammonium bromide was added, and the mixture was stirred at room temperature for 10 min. Then, 1.2 g of phenolic resin and 0.8 ml of formaldehyde were added, and the mixture was stirred to obtain a first mixed solution.
[0069] (2) Add 10 ml of tetraethyl orthosilicate to the first mixed solution, stir for 1 hour, put into 100 ml of polytetrafluoroethylene liner, and react at 100°C for 24 hours to obtain a second mixed solution. Cool the second mixture to 25°C, centrifuge the cooled second mixture to obtain a first composite. Place the first composite in a nitrogen environment, and carbonize it in a tubular furnace at a temperature of 800°C at a heating rate of 10°C / min for 2 hours to obtain silicon dioxide / carbon hollow microspheres.
[0070] (3) The silicon dioxide / carbon hollow microspheres were mixed with 0.5 g of magnesium powder and ground to obtain a first powder, which was placed in a magnetic boat in a nitrogen environment and carbonized in a tubular furnace at a temperature of 800 °C at a heating rate of 10 °C / min for 2 h to obtain a hollow microsphere silicon carbide composite absorbing material.
[0071] The wave absorbing performance of the composite wave absorbing materials prepared in Example 1, Example 2, Comparative Example 1 and Comparative Example 2 was tested respectively.
[0072] The thickness of the composite absorbing material in Example 1 is 2.1 mm, and the minimum reflection loss value RL at 11.56 GHz is min It is -48.6dB, and the effective absorption band is 4.50GHz.
[0073] The thickness of the composite absorbing material in Example 2 is 1.8 mm, and the minimum reflection loss value RL at 10.6 GHz is min It is -60.8dB, and the effective absorption band is 5.10GHz.
[0074] The thickness of the composite absorbing material in Comparative Example 1 is 2.3 mm, and the minimum reflection loss value RL at 8.9 GHz is min It is -35.6dB, and the effective absorption band is 3.2GHz.
[0075] The thickness of the composite absorbing material in Comparative Example 2 is 2.5 mm, and the minimum reflection loss value RL at 9.6 GHz is min It is -32.5dB and the effective absorption band is 2.8GHz.
[0076] According to the test results of the wave absorption performance, by comparing the above embodiments and the comparative examples, it can be seen that the composite wave absorbing materials in embodiments 1 and 2 have a strong absorption capacity for electromagnetic waves, and the composite wave absorbing materials in embodiments 1 and 2 can absorb a wider range of electromagnetic frequencies, effectively reducing the radiation effect of electromagnetic waves. By comparing embodiment 1 and comparative example 1, the silicon carbide microspheres of the composite wave absorbing material in comparative example 1 are non-hollow structures, and there is no first carbon layer inside the silicon carbide microspheres, and there is no second carbon layer on the outer surface. The loss mechanism of silicon carbide itself is relatively simple, the band gap is wide, the dielectric properties are weak, and the absorption capacity for electromagnetic waves is relatively weak. By comparing embodiment 1 and comparative example 2, bacterial cellulose is not added in comparative example 2, so that the outermost layer of the composite wave absorbing material in comparative example 2 does not include a carbon nanofiber layer. Compared with the composite material in embodiment 1, the composite wave absorbing material in comparative example 1 has fewer absorption paths for electromagnetic waves, and electromagnetic waves are not prone to more scattering, so that electromagnetic waves cannot be fully absorbed and lost. Compared with embodiment 1, the wave absorption performance of the composite wave absorbing material prepared in comparative example 2 is poor.
[0077] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit them. Under the concept of the present application, the technical features in the above embodiments or different embodiments can also be combined, the steps can be implemented in any order, and there are many other changes in different aspects of the present application as described above, which are not provided in detail for the sake of simplicity. Although the present application has been described in detail with reference to the aforementioned embodiments, a person of ordinary skill in the art should understand that the technical solutions described in the aforementioned embodiments can still be modified, or some of the technical features can be replaced by equivalents. These modifications or replacements do not deviate the essence of the corresponding technical solutions from the scope of the technical solutions of the embodiments of the present application.
Claims
1. A method for preparing a hollow microsphere silicon carbide composite absorbing material, characterized in that: include: Deionized water, anhydrous ethanol and ammonia water are mixed, a surfactant is added, and the mixture is stirred evenly, and then a phenolic resin and a formaldehyde solution are added and mixed to obtain a first mixed solution; Providing a silicon source, adding the silicon source to the first mixed solution, stirring, sealing, and reacting at a first preset temperature for a preset time to obtain a second mixed solution, centrifuging the second mixed solution to obtain a first composite, and subjecting the first composite to a carbonization treatment to obtain silicon dioxide / carbon hollow microspheres; Providing purified bacterial cellulose, mixing the bacterial cellulose with the silica / carbon hollow microspheres and freeze-drying them to obtain a second composite; The second composite is mixed with magnesium powder and then ground to obtain a first powder, and the first powder is subjected to a secondary carbonization treatment to obtain a hollow microsphere silicon carbide composite absorbing material.
2. The preparation method according to claim 1, characterized in that: The providing of purified bacterial cellulose comprises: The bacterial cellulose is soaked in an alkaline solution with a concentration of 0.2 mol / L to 0.5 mol / L, and is water-bathed at a temperature of 60°C to 100°C for 2h to 4h, and then the bacterial cellulose soaked in the alkaline solution is washed with deionized water until it is neutral to obtain the purified bacterial cellulose.
3. The preparation method according to claim 1, characterized in that: The step of adding the silicon source to the first mixed solution, stirring, sealing, and reacting at a first preset temperature for a preset time to obtain a second mixed solution, and centrifuging the second mixed solution to obtain a first complex comprises: Adding the silicon source to the first mixed solution, stirring, sealing, and reacting at a temperature of 80° C. to 120° C. for 20 h to 30 h to obtain the second mixed solution; The second mixed liquid is cooled to 20°C to 25°C, and the cooled second mixed liquid is centrifuged to obtain a precipitate, and the precipitate is washed 3 to 5 times with anhydrous ethanol and deionized water, and the washed precipitate is placed in a drying oven at a temperature of 50°C to 80°C and dried for 10 hours to 15 hours to obtain the first complex.
4. The preparation method according to claim 1, characterized in that: The step of subjecting the first composite to a carbonization treatment comprises: The first composite is placed in an inert gas environment and carbonized in a tubular furnace at a temperature of 600° C. to 1000° C. for 2 to 3 hours, and the heating rate of the tubular furnace is 5° C. / min to 15° C. / min.
5. The preparation method according to claim 1, characterized in that: The step of subjecting the first powder to a secondary carbonization treatment comprises: The first powder is placed in an inert gas environment and carbonized in a tubular furnace at a temperature of 600° C. to 1000° C. for 2 to 3 hours. The heating rate of the tubular furnace is 5° C. / min to 15° C. / min.
6. The preparation method according to any one of claims 1 to 5, characterized in that: The silicon source includes at least one of ethyl orthosilicate, methyl orthosilicate, methyltrimethoxysilane and ethyltriethoxysilane.
7. The preparation method according to any one of claims 1 to 5, characterized in that: The surfactant includes at least one of cetyltrimethylammonium chloride, cetyltrimethylammonium bromide and dodecyltrimethylammonium chloride.
8. The preparation method according to claim 1, characterized in that: The mass ratio of the second composite to the magnesium powder is (6:1) to (10:1).
9. The preparation method according to claim 1, characterized in that: The amount of the phenolic resin added is 12 g / L to 18 g / L; The added amount of the silicon source is 80 ml / L to 100 ml / L.
10. The preparation method according to claim 4, characterized in that: The inert gas includes nitrogen and / or argon.
Citation Information
Patent Citations
Preparation method of silicon carbide / carbon hollow porous microsphere wave-absorbing material
CN110819302A
Method of fabricating silicon carbide
US20140209838A1
Electromagnetic wave absorbers of silicon carbide fibers
US4726980A